Penyuluhan Keluarga Sakinah Dalam Upaya Pencegahan Penceraian Akibat Judi Online - Syamsul Arifin; Tatang Aulia Rahman; Jalil, Abdul (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
The rise of online gambling in Indonesia not only has a negative impact in the form of addiction and potential criminal acts, but also carries a threat to the integrity of Muslim family households, especially in Bojonegoro district. In 2024 the divorce rate in Bojonegoro was quite high compared to other districts in East Java, recorded from the 2024 data of the Bojonegoro Religious Court 485 cases of divorce and 1,381 divorce gugat one of the reasons because of economic factors online gambling and entangled in online loans. Most divorce applications are from Kedungadem sub-district, Temayang sub-district, Dander sub-district, Tambakrejo sub-district, and Ngasem sub-district. From the explanation above, it is necessary to counsel a sakinah family in an effort to prevent divorce due to online gambling in Kedungadem sub-district, Bojonegoro Regency in an effort to reduce the number of divorces due to online gambling in Bojonegoro Regency. This program aims to provide a deeper understanding of the importance of maintaining harmony in the family and preventing divorce due to online gambling addiction. The method used is Participatory Action Research (PAR) through 3 strategies, namely: socialization, implementation, and program monitoring and evaluation. Data were collected through observation, Focused Group Discussion (FGD), interview and documentation techniques. From the results of the implementation of the service in Megale village, Kedungadem sub-district, the following results were obtained: Data was collected through observation techniques, Focused Group Discussion (FGD), interview and documentation techniques. From the results of the implementation of the service in Megale village, Kedungadem sub-district, the following results were obtained: 1) Increased awareness and knowledge about the dangers of online gambling, 2) Understanding of the concept of Sakinah Family, 3) Effective Prevention Strategy, 4) Commitment to Change. Keywords: Sakinah Family, Divorce, Online Gambling. Abstract Maraknya judi online di Indonesia bukan hanya membawa dampak negatif berupa kecanduan dan potensi tindak kriminal, tetapi juga membawa ancaman keutuhan rumah tangga keluarga muslim khususnya kabupaten Bojonegoro. Pada tahun 2024 angaka penceraian di Bojonegoro cukup tinggi dibandingka dengan kabupaten di Jawa Timur lainnya, tercatat dari data 2024 Pengadilan Agama Bojonegoro 485 kasus cerai talak dan 1.381 cerai gugat salah satu alasan sebab faktor ekonomi judi online dan terjerat pinjaman online. Pengajuan penceraian yang paling banyak dari kecamatan Kedungadem, kecamatan Temayang, kecamatan Dander, kecamatan Tambakrejo, dan kecamatan Ngasem. Dari pemaparan diatas, maka diperlukan penyuluhan keluarga sakinah dalam upaya pencegahan penceraian akibat judi online di kecamatan kedungadem kabupaten Bojonegoro dalam upaya menurunkan angka penceraian akibat judi online di Kabupaten Bojonegoro. Program ini bertujuan untuk memberikan pemahaman yang lebih dalam tentang pentingnya menjaga keharmonisan dalam keluarga dan mencegah perceraian akibat kecanduan judi online. Metode yang digunakan adalah Participatory Action Research (PAR) melalui 3 strategi yaitu: sosialisasi, pelaksanaan, serta monitoring dan evaluasi program. Data dikumpulkan melalui teknik observasi, Focused Group Discussion (FGD), wawancara dan teknik dokumentasi. Dari hasil pelaksanaan pengabdian di desa Megale, kecamatan Kedungadem, didapatkan hasil sebagai berikut: 1) Peningkatan kesadaran dan pengetahuan tentang bahaya judi online, 2) Pemahaman tentang konsep Keluarga Sakinah, 3) Strategi Pencegahan yang Efektif, 4) Komitmen untuk Perubahan Keywords: Keluarga Sakinah, Penceraian, Judi Online.